Diagnostic ability of the Timed Up & Go test for balance impairment prediction in chronic obstructive pulmonary disease - Chalerm Liwsrisakun (2020)
© Journal of Thoracic Disease. All rights reserved. Background: Balance assessment is now recommended by clinical practice guidelines, specific tests have yet to be suggested. The Timed Up and Go (TUG) test is a simple measure of balance status and functional mobility. Nowadays, we need more data of an optimum cut off point of TUG time for detecting balance impairment in patients with chronic obstructive pulmonary disease (COPD). Thus the aim of this study was to evaluate the diagnostic ability relative to balance impairment of the TUG in subjects with COPD. Methods: The cross-sectional study was conducted in stable COPD patient at Maharaj Nakorn Chiang Mai Hospital, Chiang Mai, Thailand from November 2015 to October 2017. Balance impairment test was measured using the Berg Balance Scale (BBS), a score of ≤45 indicates balance impairment. The TUG was evaluated using sensitivity, specificity, positive likelihood ratio (LR+), negative likelihood ratio (LR?), Youden's index, and the area under receiver operating characteristic curve (AUROC) from various points of TUG to identify the optimum cut-off point for detecting balance impairment. Multivariable logistic regressions were performed to identify the optimum cut off point of TUG test time for prediction of balance impairment in COPD. Results: One hundred and eighteen smoking related COPD subjects 86 (72.9% male) with a mean age of 73.5±8.1 years were included in this study. Univariable analysis showed that the AUROC of TUG test to indicate those who had impaired balance was 0.93 [95% confidence interval (CI): 0.88, 0.98]. A cut off point of TUG test time ≥12 seconds had sensitivity, specificity, LR+, LR?, Youden's index, and AUROC of 95.8%, 90.4%, 10.01, 0.05, 86.2, and 0.93 for detecting balance impairment, respectively. Multivariable analysis identified the TUG test time ≥12 seconds was the best predictor of balance impairment in COPD patients with adjusted risk ratio (RR) of 25.2 (95% CI: 1.6, 312.0, P=0.021) and, the AUROC was 0.98 (95% CI; 0.96, 1.00). Conclusions: Our study indicates the TUG test time ≥12 seconds has a high diagnostic ability for balance impairment prediction in COPD. The result supports a potential role for this simple test to be incorporated into routine COPD assessment to stratify patients' balance.